Vascular leukoencephalopathy observed in a patient with fetal alcohol spectrum disorder: An association not yet understood - Julie Gallien; Nadia Bouhamdani; Mahée Côté; Dominique Bouhamdani; M'Hamed Belkhodja; Nicole Leblanc; Ludivine Chamard-Witkowski (Brain Disorders)
Fetal alcohol spectrum disorder (FASD) encompasses a broad range of physical and neurological impairments resulting from prenatal alcohol exposure (PAE). While the neurological consequences of FASD are well documented, its potential association with vascular leukoencephalopathy (VL) remains poorly documented and incompletely understood. This case report presents a unique case of VL documented in a 20-year-old female diagnosed with FASD at 11 years of age, offering new insights into this underrecognized and potentially emerging association. The patient had several neurological and neurodevelopmental concerns starting in infancy, which prompted a number of brain Magnetic Resonance Imaging (MRI) scans throughout life. More recently, atypical neurological examination and comorbidities led to a referral to the neurology department to investigate a possible diagnosis of multiple sclerosis. Neurological evaluation, which included ordering a new MRI and reviewing previous scans, confirmed the presence of progressive white matter lesions suggestive of VL. Despite an extensive diagnostic workup, including genetic, metabolic, and autoimmune testing, no alternative etiology was identified. The patient’s clinical history, neurodevelopmental profile, and confirmed PAE raised the possibility of VL being associated with FASD as the most plausible explanation. This case highlights the potential vascular consequences of PAE, including disrupted angiogenesis, cerebral hypoperfusion, and increased blood-brain barrier permeability, mechanisms that mirror those seen in VL. As such, it emphasizes the importance of recognizing this possible association in a clinical setting. Early neuroimaging in FASD patients may facilitate timely detection of subclinical vascular pathology, guide treatment strategies, and help mitigate long-term neurological risks. Documenting such cases is crucial to expanding clinical awareness and supporting future research.